Characterization of Triticum turgidum sspp. durum, turanicum, and polonicum grown in Central Italy in relation to technological and nutritional aspects - Palombieri, Samuela; Bonarrigo, Marco; Cammerata, Alessandro; Quagliata, Giulia; Astolfi, Stefania; Lafiandra, Domenico; Sestili, Francesco; Masci, Stefania (Frontiers in Plant Science, 2023)
Introduction Wheat is a staple food, with the two most common species being Triticum aestivum and Triticum turgidum ssp. durum. Moreover, the latter, T. turgidum, includes other tetraploid subspecies, among which the sspp. turanicum (Khorasan wheat) and polonicum (Polish wheat), whose importance has increased in the last decades, representing alternative crops for marginal areas, in addition to being a source of genetic diversity. Methods In this work, different accessions of these three subspecies of T. turgidum have been grown in 2 years in the same environment and have been characterized for technological properties and factors affecting nutritional quality, such as fiber amount and the content of micro- and macro-nutrients in grains, and for root morphological traits. Results These analyses allowed the identification, in particular, of a Polish wheat accession showing better technological performances, a higher amount of positive micro- and macro-elements, and a lower amount of toxic cadmium. The modern variety Svevo and the Polish Pol2 showed the lowest and the highest shoot:root ratio, respectively. The high shoot:root ratio in Pol2 was mainly attributable to the decrease in root growth. Although Pol2 had a lower root biomass, its particular root morphology made it more efficient for nutrient uptake, as evident from the greater accumulation of micro- and macro-nutrients. Discussion These results underline that it is not possible to draw general conclusions about the difference between primitive and modern wheats, but rather a case-by-case approach should be chosen.